1997
DOI: 10.1073/pnas.94.19.10199
|View full text |Cite
|
Sign up to set email alerts
|

Effects of p 53 mutations on apoptosis in mouse intestinal and human colonic adenomas

Abstract: We have examined the effects of inactivation of the p53 tumor suppressor gene on the incidence of apoptotic cell death in two stages of the adenoma-to-carcinoma progression in the intestine: in early adenomas where p53 mutations are rare and in highly dysplastic adenomas where loss of p53 occurs frequently. Homozygosity for an inactivating germline mutation of p53 had no effect on the incidence or the rate of progression of Apc Min͞؉ -induced adenomas in mice and also did not affect the frequency of apoptosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
30
2
4

Year Published

1998
1998
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(39 citation statements)
references
References 44 publications
(51 reference statements)
3
30
2
4
Order By: Relevance
“…In cells which have a relatively limited DNA repair capacity or are approaching the end of their replicative lifespan anyway, it may be safer to opt for irreversible senescence rather than take the risk of reentering the cell cycle with only partially repaired damage. The broad relevance of senescence to p53-mediated tumor suppression is also suggested by a recent study on colon cancer in mice (Fazeli et al, 1997).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In cells which have a relatively limited DNA repair capacity or are approaching the end of their replicative lifespan anyway, it may be safer to opt for irreversible senescence rather than take the risk of reentering the cell cycle with only partially repaired damage. The broad relevance of senescence to p53-mediated tumor suppression is also suggested by a recent study on colon cancer in mice (Fazeli et al, 1997).…”
Section: Discussionmentioning
confidence: 92%
“…In response to radiation or genotoxic drugs, p53 mediates either growth arrest or apoptosis which prevent the replication of a mutated genome by either eliminating cells with DNA damage through programmed cell death or by allowing DNA repair to take place before DNA synthesis during S phase begins (for review see Gottlieb and Oren, 1996;Ko and Prives, 1996). Although p53-mediated apoptosis may be considered a major avenue for avoiding cancer, recent studies on a mouse model of colon cancer indicate that loss of p53 does not correlate with reduced apoptosis and that wt p53 can retard the progression of adenoma to carcinoma by mechanisms other than apoptosis (Fazeli et al, 1997). Such mechanisms may be related to p53-mediated growth arrest, particularly if this arrest becomes irreversible leading to replicative senescence (Smith and PereiraSmith, 1996;Atadja et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, whereas apoptosis was proven to be the critical determinant of p53's protective effect in lymphoma and in choroid plexus tumors, 121,122 it was deemed practically irrelevant in intestinal track cancer, where maintenance of genomic stability by p53 is probably implicated instead. 123 As illustrated in this review, one may have to approach p53 not as a simple switch that determines cell fate single-handedly, but rather as a component, albeit an important one, in an intricate network of signals and molecular interactions. 9 The actual output of this network, and the particular contribution of p53 to that output, will inevitably depend not only on p53, but largely also on its multiple interactions with the many other players in this complex game of life and death, normal growth control and cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to growth arrest the damaged cell can also undergo apoptosis; the relative contribution of apoptosis versus growth arrest to prevention of tumorigenesis may vary among di erent tissues and cell types (Hansen and Oren, 1997). Recent studies on colon cancer in mice of p537/7 and p53+/+ background indicate that p53 may retard tumor progression by yet another mechanism based on irreversible growth arrest which may lead to senescence (Fazeli et al, 1997) and it was also shown that induced p53 expression in EJ cells was shown to promote cell senescence (Sugrue et al, 1997). The choice between reversible growth arrest, apoptosis and senescence as a result of p53 function is under extensive study and may depend on cell type and developmental stage (Bates and Vousden, 1996).…”
Section: Introductionmentioning
confidence: 99%